Scientific and pedagogical schools of internal medicine and general practice in the single education system - O. M. Drapkina; S. Yu. Astanina; R. N. Shepel; O. S. Abramovskikh; M. M. Abdurakhmanov; E. V. Averyanova; V. N. Antonov; L. R. Akhmadeeva; A. E. Bagri; A. B. Bakirov; B. A. Bakirov; N. A. Belyakova; et al. (Кардиоваскулярная терапия и профилактика, 2025)
The article analyzes approaches to defining scientific and academic schools, as well as defines criteria and specifics of educational research schools of internal medicine and general practice that have developed in higher education institutions in Russia and abroad. A review of the speeches of 86 representatives of educational research schools of internal medicine and general practice at the IV International Researchto-Practice Forum "Educational Research Schools of Internal and Preventive Medicine" is given. Panel discussion meeting resolutions with the main conclusions and proposals for the development of internal medicine schools as teams of like-minded people working on the future of medical education within single educational space of physicians, internists, general practitioners (family doctors) are presented.